(3eNJUQ cJGH GdeDed ddQO Edi GdCeQ GdCeds - (3eLghds; (3GHf CHj TGeI GdebOSjs
(3ChdgG (B:s
(3CeG HYO aEf GdYde fOQSJ CYdGeg hbd ai gPg GdCReGf EJbGfg hGMcGeg hBd Hg GdEgeGd Edi Cf YOe EMJQGeg s
(3BNQgG (B:s
(3bGd CHh HcQ GdCKQe cfG YfO GdHhjWi aPcQJ MOjK YeGQ ai GdJje aCNP GdScjf hMJg ef cJGHg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs